2018
DOI: 10.1242/dmm.036673
|View full text |Cite
|
Sign up to set email alerts
|

The big picture: exploring the metabolic cross-talk in cancer

Abstract: Metabolic reprogramming is now well established as one of the hallmarks of cancer. The renewed interest in this topic has spurred a remarkable advance in our understanding of the metabolic alterations in cancer cells and in the tumour microenvironment. Initially, this research focussed on identifying the metabolic processes that provided cancer cells with building blocks for growth or to prevent oxidative damage and death. In addition to providing detailed insight into the mechanisms by which oncogenic signall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Pancreatic cancer is regarded as the most common and lethal disease of the digestive tract tumors. Altered metabolism and tumor microenvironment are considered as the Hallmarks of cancer 13 . Given the above considerations, deep thinking about metabolic dysregulation in patients with pancreatic cancer could be a novel discovery of tumor therapeutic targets 14 .…”
Section: ■ Discussionmentioning
confidence: 99%
“…Pancreatic cancer is regarded as the most common and lethal disease of the digestive tract tumors. Altered metabolism and tumor microenvironment are considered as the Hallmarks of cancer 13 . Given the above considerations, deep thinking about metabolic dysregulation in patients with pancreatic cancer could be a novel discovery of tumor therapeutic targets 14 .…”
Section: ■ Discussionmentioning
confidence: 99%
“…The diet modulates the efficacy of CRC by reshaping the TME. As reported by Iwamoto et al, the addition of lipids to the TME prevented the tumor inhibitory effect of anti-angiogenic therapy [247,248]. The ketogenic diet, low in carbohydrates but rich in proteins and fat, reduced tumor size in mouse models of colon carcinoma, and recently, it was found that this kind of diet can enhance the anti-cancer therapy efficacy of PI3Kα inhibitors [248,249].…”
Section: Microbiota Reshape the Tumor Microenvironment (Tme) In Crcmentioning
confidence: 78%
“…Aerobic glycolysis is characterized by increased glucose uptake and lactate production, and it is the most common feature of cancer metabolism ( Bazylianska et al, 2021 ; Kalezic et al, 2021 ). Natural compounds that interact with components of glycolytic pathway can reduce the cancer cell’s ability to synthesize nucleotides, proteins, or lipids ( Schulze and Yuneva, 2018 ). The reduction in the glucose uptake, glycolytic enzyme activities and the consequent lactate production is a very interesting effect of V. album MT, since this treatment probably interrupts the Warburg effect ( Schulze and Harris, 2012 ).…”
Section: Discussionmentioning
confidence: 99%